Peran Karakteristik Pemilik, Hubungan Dengan Pelanggan, Komitmen Perilaku, dan Orientasi Usaha Terhadap Kinerja Keuangan UKM - Hadi Ismanto; Shalihul Aziz Widya Irawan (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2018)
Many small and medium enterprises (SMEs) in Indonesia still experience failure and have less attention on how to maintain business performance stability. There are a lot of business owners who only focus on the benefit value and the incurred cost to run the short-term business operation and pay less attention to financial performance. This study aims to examine the influence of owner characteristics, customer relationship, and behavioral commitment to SME’s financial performance through the mediating role of business orientation. The sample consists of 160 SMEs of Troso Ikat weaving which are selected through purposive sampling technique and the data are analysed using Structural Equation Modeliing (SEM). The results show that owner characteristics reflected by the ambition, imagination, aggressiveness, and confidence, and customer relations indicated by trust level , commitment, and satisfaction have a positive effect on business orientation and financial performance. In addition, business orientation also has a positive impact on the performance of SMEs. Meanwhile, behavioral commitment has no direct effect on business orientation or financial performance.